Can active learning principles be applied to the bioscience assessments of nursing students? A review of the literature. (February 2016) - Bakon, Shannon; Craft, Judy; Christensen, Martin; Wirihana, Lisa
Summary: Objectives: To explore if active learning principles be applied to nursing bioscience assessments and will this influence student perception of confidence in applying theory to practice? Design and Data Sources: A review of the literature utilising searches of various databases including CINAHL, PUBMED, Google Scholar and Mosby's Journal Index. Methods: The literature search identified research from twenty-six original articles, two electronic books, one published book and one conference proceedings paper. Results: Bioscience has been identified as an area that nurses struggle to learn in tertiary institutions and then apply to clinical practice. A number of problems have been identified and explored that may contribute to this poor understanding and retention. University academics need to be knowledgeable of innovative teaching and assessing modalities that focus on enhancing student learning and address the integration issues associated with the theory practice gap. Increased bioscience education is associated with improved patient outcomes therefore by addressing this "bioscience problem" and improving the integration of bioscience in clinical practice there will subsequently be an improvement in health care outcomes. Conclusion: From the literature several themes were identified. First there are many problems with teaching nursing students bioscience education. These include class sizes, motivation, concentration, delivery mode, lecturer perspectives, student's previous knowledge, anxiety, and a lack of confidence. Among these influences the type of assessment employed by the educator has not been explored or identified as a contributor to student learning specifically in nursing bioscience instruction. Second that educating could be achieved more effectively if active learning principles were applied and the needs and expectations of the student were met. Lastly, assessment influences student retention and the student experience and as such assessment should be congruent with the subject content, align with the learning objectives and be used as a stimulus tool for learning. Highlights: The type of assessment used has not been explored as a contributor to student learning in nursing bioscience instruction. Bioscience has been identified as an area that nurses struggle to learn and apply to clinical practice. Educators need to be knowledgeable of innovative assessing modalities that focus on enhancing student learning. Assessment should be congruent with the subject content, and be used as a stimulus tool for learning.